Bovine neosporosis in dairy cattle from the southern highlands of Ecuador - Maldonado Rivera, J.E.; Vallecillo, A.J.; Pérez, C.L; Cirone, Karina Mariela; Dorsch, M.A.; Scioli, V.; Hecker, Yanina; Fiorani, Franco; Canton, German Jose; Moore, Prando Dadin (Elsevier, 2020)
The aim of this study was to describe bovine neosporosis in dairy cattle from the Sierra region, Ecuador. A case-control study was performed on 841 dairy cattle from 5 dairy herds. The overall seroprevalence was 23.4% having significant association between abortion and seropositivity (p < .05). Additionally, 46 fetuses were recovered from a local slaughterhouse to evaluate the frequency of vertical transmission. Seventeen and 3 fetuses were positive by PCR and had compatible histopathological lesions, respectively. N. caninum infection must be considered as a relevant cause of reproductive losses in Ecuador.